2023
DOI: 10.1158/0008-5472.can-22-1622
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CaMKK2 Inhibits Actin Cytoskeletal Assembly to Suppress Cancer Metastasis

Abstract: Triple-negative breast cancers (TNBCs) tend to become invasive and metastatic at early stages in their development. Despite some treatment successes in early stage localized TNBC, the rate of distant recurrence remains high, and long-term survival outcomes remain poor. In a search for new therapeutic targets for this disease, we observed that elevated expression of the serine/threonine kinase calcium/calmodulin (CaM)-dependent protein kinase kinase 2 (CaMKK2) is highly correlated with tumor invasiveness. In va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Our recent work further demonstrated that PDE4D enzymes are expressed in activated HSCs in human and mouse livers and play a role in promoting cytoskeleton remodeling and HSC migration [58]. Notably, PDE1a has also been shown to regulate cell motility and the migration of cancer cells via cGMP/PKG [59]. Relevant to ALD, our studies identified the PDE4B-dependent downregulation of cAMP signaling as a pathogenic player in exaggerated responses of monocytes/macrophages to endotoxin on ALD [21,52].…”
Section: Discussionsupporting
confidence: 54%
“…Our recent work further demonstrated that PDE4D enzymes are expressed in activated HSCs in human and mouse livers and play a role in promoting cytoskeleton remodeling and HSC migration [58]. Notably, PDE1a has also been shown to regulate cell motility and the migration of cancer cells via cGMP/PKG [59]. Relevant to ALD, our studies identified the PDE4B-dependent downregulation of cAMP signaling as a pathogenic player in exaggerated responses of monocytes/macrophages to endotoxin on ALD [21,52].…”
Section: Discussionsupporting
confidence: 54%
“…EP4 and CaMKK2 are known to correlate with the progression and survival rates in cancers such as vulvar cancer and breast cancer 43 , 44 . To the best of our knowledge, there have been no reports in oral cancer linking EP4, CaMKK2, or CALML6 with cancer progression or survival rates, indicating a need for further investigation (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is localized at the ES and has been reported to interact with tight junction proteins such as ZO1 (56), but its role in regulating actin assembly in the ES is unknown. CAMKK2 is a kinase that regulates actin assembly to guide cell adhesion, migration, and morphogenesis during tissue homeostasis and cancer metastasis (57)(58)(59)(60). PPP1R9A (also known as neural-specific F-actin-binding protein, NEURABIN1) is a kinase that binds to Factin to promote neurite formation and synaptic transmission (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…We thus compared our data with published Sertoli cell-expressing genes (53,54), and identified 27 Sertoli cellenriched genes that are alternatively spliced upon PTBP1 deficiency (Supplementary Table 6). Strikingly, 8 of them (Espn, Tnik, Gm14569, Ppp1r9a, Appl2, Rab11fip3, Phactr2, and Camkk2) were reported to be functionally required for actin cytoskeleton organization (18,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). Except for Espn, splicing of more than one exon of each gene was affected by PTBP1 deletion, either in exon skipping or mutually exclusive AS (Figure 4A).…”
Section: Loss Of Ptbp1 Altered the Splicing Of Actin Cytoskeleton Reg...mentioning
confidence: 99%